(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study investigated the effects of job design dimensions on organizational performance of public sector organization in Cross River State using Cross River State Board of Internal Revenue Service, Calabar, for the study. The study sought to examine the extent to which skill variety, task identity, task significance, task autonomy as well as feedback significantly affects organizational performance (employees’ motivation, job satisfaction, employees’ commitment, employees’ involvement) of public sector organizations in the state. The study adopted survey research design. The population of the study was four hundred (400). The sample size was 196 respondents from the Cross River State Board of Internal Revenue Service, Calabar, determined by Krejcie and Morgan Table of 1970. The study revealed that skill variety, task identity, task significance, task autonomy as well as job feedback significantly affects organizational performance of public sector organizations in the state. Based on the findings, the study recommended that the government and management of public sector organizations should at all times design jobs based on skill variety, task identity and task significance in order to increase organizational performance continuously. The government as well as management should also be granting task autonomy to workers while performing their routine jobs and responsibilities, for this will in turn enhance employees as well as organizational performance steadily.